Comparison of three routes of administration of tranexamic acid in primary unilateral total knee arthroplasty: Analysis of a national database. Issue 173 (January 2019) - Xie, Jinwei; Hu, Qinsheng; Huang, Zeyu; Zhou, Zongke; Pei, Fuxing
Abstract: Introduction: The ideal route for the administration of tranexamic acid (TXA) remains undecided. This study aimed to compare the efficacy and safety of three routes of TXA following primary total knee arthroplasty (TKA). Materials and methods: We prospectively collected patients' data through the National Health Database from January 2013 to September 2017. The patients were divided into a control group, intravenous group, topical group, and combined group according to the different routes of TXA. The primary outcome was the incidence of transfusion, and secondary outcomes were total blood loss, hemoglobin level and extent of hemoglobin decrease on postoperative day 3, and incidence of complications. Results: Of the total of 7133 primary TKA procedures collected, 4201 employed TXA and 2932 did not. The transfusion rate was 19.8% in the control group and 7.5% in the topical group, significantly higher than that in the intravenous (4.0%, p < 0.001) and combined (4.2%, p < 0.01) groups. The topical group had higher blood loss (0.97 ± 0.47 L), greater reduction in hemoglobin level (31.2 ± 10.1 g/L), and lower hemoglobin level (102.6 ± 12.7 g/L) on postoperative day 3, compared with the intravenous and combined groups (p < 0.05 for all). The differences between the intravenous and combined groups were not significant (p > 0.05). The incidence of deep vein thrombosis in the topical group (1.1%) was significantly higher than that in the control (0.4%, p = 0.007) and intravenous groups (0.3%, p = 0.003). Conclusion: Intravenous and combined administration of TXA was equivalent in reducing blood loss and transfusion requirement, and superior to topical routes. Highlights: TXA can reduce blood loss and transfusion, regardless of topical, IV, or combined use. IV or combined use was equivalent in efficacy but superior to topical use alone. IV and combined route was safe, while topical TXA might increase the risk of VTE.